2011
DOI: 10.5653/cerm.2011.38.2.103
|View full text |Cite
|
Sign up to set email alerts
|

Adverse pregnancy outcomes with assisted reproductive technology in non-obese women with polycystic ovary syndrome: a case-control study

Abstract: ObjectiveTo investigate adverse pregnancy outcomes in non-obese women with polycystic ovary syndrome (PCOS) compared with obese-PCOS and control groups.MethodsWomen with PCOS who underwent assisted reproductive technology (ART) from August, 2003 to December, 2007, were considered. A total of 336 women with PCOS were included in the study group and 1,003 infertile women who had tubal factor as an indication for ART were collected as controls. They were divided into four groups: a non-obese PCOS group, obese-PCO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
77
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(88 citation statements)
references
References 20 publications
6
77
5
Order By: Relevance
“…Being overweight in prepregnancy is an important predictor for the risk of perinatal complications in women with PCOS [19,20]. Another report showed that the prevalence of GDM and fetal macrosomia was significantly higher in overweight versus normal-weight women with PCOS [21]. Regarding obesity, we observed a high prevalence of GDM with glucose intolerance and high insulin secretion at preconception in overweight and obese patients with PCOS, but there was no macrosomia (data not shown).…”
Section: Discussionsupporting
confidence: 48%
“…Being overweight in prepregnancy is an important predictor for the risk of perinatal complications in women with PCOS [19,20]. Another report showed that the prevalence of GDM and fetal macrosomia was significantly higher in overweight versus normal-weight women with PCOS [21]. Regarding obesity, we observed a high prevalence of GDM with glucose intolerance and high insulin secretion at preconception in overweight and obese patients with PCOS, but there was no macrosomia (data not shown).…”
Section: Discussionsupporting
confidence: 48%
“…The miscarriage rate (the proportion of miscarriages in all clinical pregnancies) in the slow-freezing group was higher (29 vs 15.7 %), especially in the case of single embryo transfers. The miscarriage rate were higher than presented in previous studies in the case of day 3 FET cycles by Liu et al (12.6 vs 12.1 %) or Rama Raju et al (7.71 vs 9.24 %) [21,24], but it did not differ from the results of a study on the miscarriage rate after fresh embryo transfers (17.4-22.2 %) in PCO and tubal infertility [25]. The most common reason for early pregnancy miscarriages is the chromosomal abnormalities irrespective the mode of fertilization (spontaneous or ART) [26][27][28].…”
Section: Discussioncontrasting
confidence: 71%
“…Publication bias was detected significant by using the Egger test (P= 0.03). It was notable that sensitivity analysis ‘see Additional file 3: Figure S2’ with the exclusion of one study with borderline eligibility [44], did substantial decrease in insignificant heterogeneity (χ 2 : P=0.309, I 2 = 13.5%), and the difference in risk of development PIH between women with PCOS and controls remained robust [13 studies, fixed effects OR 3.43 (95% CI: 2.49–4.74), Figure 2]. Meta-regression failed to provide evidence of a significant effect between outcome and study type (retrospective vs. prospective) (P=0.17) or BMI (P= 0.54).…”
Section: Resultsmentioning
confidence: 99%